1998
DOI: 10.1159/000023893
|View full text |Cite
|
Sign up to set email alerts
|

Differential Production of Chemokines and Their Role in Neutrophil Infiltration in Rat: Allergic Inflammation

Abstract: Background: Recently we demonstrated that activated rat macrophages produced neutrophil chemotactic factors (chemokines) including cytokine-induced neutrophil chemoattractant (CINC)-1, CINC-2α, CINC-2β, CINC-3/rat macrophage inflammatory protein (MIP)-2 and rat MIP-1α (rMIP-1α). Methods: In the present study, by using an enzyme-linked immunosorbent assay specific for each chemokine, we determined the levels of the chemokines in the pouch fluid (inflammatory site) of the fluorescein isothiocyanate-labeled ovalb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…From these results, it has been concluded that MIP-1α, together with CINCs, plays an important role in infiltration of neutrophils into inflammatory sites in rats. However, it has also been reported that CINCs, but not MIP-1α, play an important role in neutrophil infiltration into the site of FITC-ovalbumin-induced allergic inflammation in rats (21). The discrepancy between the models is unclear at the present time but may depend on different inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…From these results, it has been concluded that MIP-1α, together with CINCs, plays an important role in infiltration of neutrophils into inflammatory sites in rats. However, it has also been reported that CINCs, but not MIP-1α, play an important role in neutrophil infiltration into the site of FITC-ovalbumin-induced allergic inflammation in rats (21). The discrepancy between the models is unclear at the present time but may depend on different inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 75%
“…In addition to CINCs, MIP-1α, a CC chemokine, was also purified as a neutrophil chemoattractant from conditioned medium of lipopolysaccharide (LPS)-stimulated rat macrophages (25). It has been demonstrated that CINCs and MIP-1α are potent chemoattractants for rat neutrophils in vitro and in vivo (21,23,32,37,40).…”
mentioning
confidence: 99%
“…These cytokines are potent chemotactic factors for rat neutrophils both in vitro and in vivo and can be induced by LPS, IL-1, and TNF-␣ (Watanabe et al, 1991). Furthermore, CINCs have similar ability to induce chemotaxis and to activate rat neutrophils, suggesting that their contribution to neutrophil infiltration depends on the amount of each present in a certain inflammatory site (Nakagawa et al, 1998). Thus, our data that only CINC-3 mRNA expression is increased in lung tissue from capsaicinpretreated rats upon antigen exposure indicate a pivotal role for this cytokine in the airways neutrophil infiltration of the capsaicin neonatal model.…”
Section: Discussionmentioning
confidence: 99%
“…When the i.t. addition of a potent neutrophil chemokine, CINC-1 (a member of the IL-8 family), in combination with OVA was examined in terms of its ability to induce an LAR, CINC-1 (up to 100-fold more than C5a desArg) was incapable of LAR induction when used in combination with the Ag, thus suggesting that C5a plays a specific role in the LAR in this model (36). Nevertheless, CINC-1 plus OVA stimulation resulted in the accumulation of as many granulocytes in the bronchial submucosa as were noted with C5a desArg plus OVA.…”
Section: Discussionmentioning
confidence: 99%